PERANG PASIFIK DALAM INGATAN PENDUDUK MOROTAI SEPTEMBER 1944-AGUSTUS 1945 - Takou, Milton Milton (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Thesis titled, "Pacific War In Memory Population Morotai September 1944-August 1945" is part of a series of Allied counterattack under the control of General Douglas MacArthur who chose the island of Morotai in North Maluku Allied military base, especially air strikes to the seizure of the Philippines and the efforts of neutralizing force enemy in eastern Indonesia. War involving the two powers, the Allies on the one hand and Japan on the other hand is told by residents Morotai experience and resources of the Pacific war literature in Morotai as confirmation. The focus of this study discusses the first, the war between the Allies and Japan at Morotai and the effect on the lives of the natives during the period September 1944 to February 1945. Second, the general state of the Allies and the natives in Borneo Operation period until the end of the war, February-August 1945. The results of this study indicate when the first period September 1944-February 1945, indigenous Morotai suffered badly from Allied-Japanese war, while in the second period, February-September 1945 socio-economic conditions began to improve indigenous, indigenous workers can work at Base Camp Allied. The schools will be opened, and daily activities as usual. Or the general state of the natives is much better than the Japanese occupation. Keywords:Japan, Allied, Indigenous, Base Camp